1984
DOI: 10.1128/jb.157.2.375-379.1984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of a Neurospora crassa RNase purified from cultures undergoing each of three different states of derepression

Abstract: Extracellular RNase N4 from Neurospora crassa is derepressible by limitation of any of the three nutrient elements obtainable from RNA. We have purified and characterized the enzyme from cultures grown under each of the three states of derepression. The purification procedure consisted of an ultrafiltration step, cation-exchange chromatography, and gel filtration. We found only one enzyme (N4) that hydrolyzed RNA at pH 7.5 in the presence of EDTA in culture filtrates from nitrogen-, phosphorus-, or carbon-limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This indicated that cationrequiring nuclease activity in culture filtrates was not being detected by our assay. In addition, when RNase activity was purified from several culture conditions, only one polypeptide (N4) was found to be active in the presence of EDTA (17). These observations imply that the RNase assay employed in this communication was specific for RNase N4.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This indicated that cationrequiring nuclease activity in culture filtrates was not being detected by our assay. In addition, when RNase activity was purified from several culture conditions, only one polypeptide (N4) was found to be active in the presence of EDTA (17). These observations imply that the RNase assay employed in this communication was specific for RNase N4.…”
Section: Resultsmentioning
confidence: 63%
“…RNase activity in culture filtrates. We have detected in culture filtrates of N. crassa a RNase (N4) that differed from the only previously reported extracellular RNase from N. crassa, N1, (9,15,17). The N,, found in stationary-phase culture filtrates, was reported to be phosphate derepressible (13), but those studies used cultures grown for several days, and the enzymes detected were not well characterized.…”
Section: Resultsmentioning
confidence: 65%
“…Nevertheless, Neurospora crassa is probably the best-studied filamentous fungus in terms of biochemistry and genetics, and is also a valuable model system for molecular research. Neurospora crassa produces many hydrolytic enzymes, including cellulases (Eberhart et al, 1977;Yazdi et al, 1990), nucleases (Lindberg & Drucker, 1984), proteases (Cohen & Drucker, 1977), amylase (Sigmund et al, 1985), xylanase (Mishra et al, 1984), glucosidases (Eberhart & Beck, 1973) and others, which have been the focus of intense research. These studies are relevant to our understanding of the genetics, enzymology, regulatory properties and other characteristics of fungal hydrolases.…”
Section: Introductionmentioning
confidence: 99%